Characterization of a macroporous polyvinyl alcohol scaffold for the repair of focal articular cartilage defects. (2nd May 2012) - Ng, Kenneth W.; Torzilli, Peter A.; Warren, Russell F.; Maher, Suzanne A.
Abstract Focal cartilage defects reduce the ability of articular cartilage to resist mechanical loading and provide lubrication during joint motion. The limitations in current surgical treatments have motivated the use of biocompatible scaffolds as a future treatment option. Here we describe a second generation macroporous, polyvinyl alcohol (PVA) scaffold with independently tunable morphological and mechanical properties. The compressive moduli of the PVA scaffold increased with increasing polymer concentration and applied compressive strain, with values in the range for human articular cartilage (HA > 1000 kPa, EY > 500 kPa). Scaffolds also possessed strain‐dependent permeability and Poisson's ratio. The interconnected macroporous network was found to facilitate chondrocyte seeding and proliferation through the scaffold over one week in culture. Overall, these promising characteristics demonstrate the potential of this macroporous scaffold for future studies in focal cartilage defect repair. Copyright © 2012 John Wiley & Sons, Ltd.